2017
DOI: 10.1007/s00127-017-1364-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level factors associated with mental health in Rwandan youth affected by HIV/AIDS

Abstract: Purpose Prevention of mental disorders worldwide requires a greater understanding of protective processes associated with lower levels of mental health problems in children who face pervasive life stressors. This study aimed to identify culturally appropriate indicators of individual-level protective factors in Rwandan adolescents where risk factors, namely poverty and a history of trauma, have dramatically shaped youth mental health. Methods The sample included 367 youth aged 10–17 in rural Rwanda. An earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Among the research studies that have looked into individual attributes of PLWH in the context of resilience frameworks, several have explored the lived experiences of young MSM living with HIV/AIDS. Interestingly, the findings that have been documented from these studies revealed individual attributes that were similar, akin, or thematically related to the individual attributes that were described in this paper ( Barry et al, 2018 ; Haddad et al, 2019 ; Harper et al, 2014 ; Scorza et al, 2017 ). These included studies that have discussed: (a) the individual attribute perseverance or another finding thematically related to it such as patience ( Scorza et al, 2017 ); (b) other findings that were thematically related to the individual attribute having the right mindset (as defined and described in the Results section) such as self-acceptance, optimism, positive outlook, and taking responsibility for their health outcomes ( Barry et al, 2018 ; Harper et al, 2014 ); and (c) other findings that were thematically related to the individual attribute self-awareness with self-control such as sense of control ( Harper et al, 2014 ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Among the research studies that have looked into individual attributes of PLWH in the context of resilience frameworks, several have explored the lived experiences of young MSM living with HIV/AIDS. Interestingly, the findings that have been documented from these studies revealed individual attributes that were similar, akin, or thematically related to the individual attributes that were described in this paper ( Barry et al, 2018 ; Haddad et al, 2019 ; Harper et al, 2014 ; Scorza et al, 2017 ). These included studies that have discussed: (a) the individual attribute perseverance or another finding thematically related to it such as patience ( Scorza et al, 2017 ); (b) other findings that were thematically related to the individual attribute having the right mindset (as defined and described in the Results section) such as self-acceptance, optimism, positive outlook, and taking responsibility for their health outcomes ( Barry et al, 2018 ; Harper et al, 2014 ); and (c) other findings that were thematically related to the individual attribute self-awareness with self-control such as sense of control ( Harper et al, 2014 ).…”
Section: Discussionsupporting
confidence: 72%
“…Among the research studies that have looked into individual attributes of PLWH in the context of resilience frameworks, several have explored the lived experiences of young MSM living with HIV/AIDS. Interestingly, the findings that have been documented from these studies revealed individual attributes that were similar, akin, or thematically related to the individual attributes that were described in this paper (Barry et al, 2018;Haddad et al, 2019;Harper et al, 2014;Scorza et al, 2017). These included studies that have discussed: (a) the individual attribute perseverance or another finding thematically related to it such as patience (Scorza et al, 2017);…”
Section: Discussionmentioning
confidence: 78%
“…Taken together, these findings support convergent validity, i.e., that the scale is associated with other theoretically related variables. As described previously, more general resilience scales like the CD-RISC have demonstrated associations with mental and physical health outcomes in other studies among PLHIV [12, 15, 16]. However, it remains unclear the extent to which resilience as measured in those studies was in relation to HIV status—and hence what, precisely, was associated with those outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…Many of these studies have used resilience scales that assess general psychological resilience, i.e., not in the context of particular types of adversity. The conner-davidson resilience scale (CD-RISC) [24], a 25-item scale that was originally developed to assess responses to treatment for anxiety, depression and stress reactions, has been most frequently used [11, 12, 15, 16, 18, 23, 2527]. This scale was primarily oriented around personal qualities that enable thriving in the face of adversity (e.g., “I try my hardest on every occasion” and “I can adapt to change”), but also captures certain features the developers believed to underpin resilience, such as having close personal relationships and experience achieving one’s goals [24].…”
Section: Introductionmentioning
confidence: 99%
“…This reprieve further allows racial and ethnic minority MSM to sustain their perseverance to thrive even during the most challenging times after their HIV diagnosis. Research has shown that perseverance is an individual-level trait (similar to other protective factors like optimism and self-efficacy) that reduces risks of mental health problems among MSMLWH, and helps them deal with physical and psychosocial adversities related to living with HIV/AIDS [72,73].…”
Section: Discussionmentioning
confidence: 99%